2013
DOI: 10.1016/j.jsv.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the changes in the natural frequency of a pile affected by scour

Abstract: Publication informationJournal of Sound and Vibration, 332 (25): 6685-6702Publisher Elsevier Item record/more information http://hdl.handle.net/10197/6581 Publisher's statementThis is the author's version of a work that was accepted for publication in Journal of Sound and Vibration. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 27 publications
5
97
0
Order By: Relevance
“…Similar examples of this phenomenon can be found in [5,12]. Filtering the signal has the effect of removing the high frequency oscillations at the beginning of the unfiltered signal and exposing the Published in Soil Dynamics and Earthquake Engineering, 2016 (81C) pp.…”
Section: Experimental Frequency Response and Damping Ratiosmentioning
confidence: 60%
See 2 more Smart Citations
“…Similar examples of this phenomenon can be found in [5,12]. Filtering the signal has the effect of removing the high frequency oscillations at the beginning of the unfiltered signal and exposing the Published in Soil Dynamics and Earthquake Engineering, 2016 (81C) pp.…”
Section: Experimental Frequency Response and Damping Ratiosmentioning
confidence: 60%
“…In the case of bridges, most of the work to date has focused on monitoring the superstructure. More recent research has begun to focus on using these damage SoftSoft detection methodologies on sub-structural elements (see [5][6][7]). In these cases, the analyses can be quite sensitive to the soil stiffness assumed in the design where the dynamic oscillations typically remain in the small-strain region.…”
Section: Dynamic Soil-structure Interaction (Dssi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that accelerometers located on the model bridge pier performed very well at measuring the change in natural frequency as scour severity increased. Using full-scale field testing Prendergast et al [18] validated a method to detect the change in the natural frequency of a single pile affected by scour. Moreover, they suggest a method for creating soil-springs using correlations to geotechnical site data such as shearwave velocities and cone penetration tests.…”
Section: Indirect Monitoring Of Bridge Scour By Identifying Changes Imentioning
confidence: 99%
“…The compromised stability of a bridge foundation due to adverse scour hole formation gives rise to a change in the response features of a bridge such as increased pier tilting, pier settlement, changes to dynamic characteristics, increased strain at deck level, crack formation due to differential settlement among other indicators. Primarily, the change in support conditions gives rise to a change in the dynamic characteristics (Doebling et al 1996;Prendergast et al 2016b;Prendergast et al 2016a;Foti & Sabia 2011;Elsaid & Seracino 2014;Briaud et al 2011;Prendergast et al 2013), and this may become a primary indicator of performance. Vibration-based scour detection is a significant advance over the instruments discussed in Table 1, in that it focuses on measuring the response of the structure itself to the formation of scour in lieu of inferring the bridge stability from a measured scour depth.…”
Section: Shm For Scourmentioning
confidence: 99%